Augmented Reality Media About the Solar System to Improve Learning Outcomes of Fourth Grade Elementary School Students - A.A. Komang Melia Sukmawati; I Gde Wawan Sudatha; I Kadek Edi Yudiana (Journal of Education Technology, 2025)
The limitations of interactive and contextual learning media are one of the factors that hinder students' understanding of the solar system concept, while also contributing to low learning outcomes. This study aims to develop and test Augmented Reality (AR)-based learning media that are valid, practical, and effective in improving students' learning outcomes on solar system material in IPAS content. The type of research used is development research (Research and Development) with the ADDIE model. The research subjects consist of 24 sixth-grade elementary school students. Data collection techniques included expert validation using a rating scale questionnaire, practicality testing by teachers and students through questionnaires, and objective tests in the form of pre-tests and post-tests to measure learning outcomes. The data obtained were analysed quantitatively through validity tests, practicality tests, and statistical tests using the Paired Sample T-Test to determine the significance of the improvement in learning outcomes. The results showed that the developed AR media had high validity and practicality and was effective in improving students' understanding and learning outcomes. The conclusion of this study indicates that AR-based media can be an innovative solution to improve the quality of learning on solar system material. The implications of this study point to the wider use of AR technology in thematic learning in elementary schools.